Polysomy and amplification of chromosome 7 defined for EGFR gene in squamous cell carcinoma of the lung together with exons 19 and 21 wild type - Couceiro,Patrícia (2010)
Purpose: The epidermal growth factor receptor (EGFR) is overexpressed in the majority of nonsmall-cell lung cancers (NSCLC) and is a major target specific EGFR tyrosine kinase inhibitors (TKIs) developed and used for the treatment of advanced NSCLC. A number of biological factors are also associated with EGFR-TKIs responsiveness. This study was focused on EGFR somatic mutations and amplifications in squamous cell lung cancer. Material and methods: Representative sections of squamous cell carcinoma were selected from 54 surgical specimens from formalin-fixed paraffin-embedded tissues and submitted to TMA construction. Determination of EGFR protein expression was done by immunohistochemistry( IHC) (Zymed, Laboratories). Fluorescence in situ hybridization (FISH) was performed with LSI EGFR/CEP 7 (Vysis; Abbott Molecular, USA). Genomic DNA was extracted from 48 cases and exon 19 was amplified by polymerase chain reaction (PCR) for search deletions and point mutations for exon 21. All cases expressed high weigh cytokeratin and were observed negativity for CK7, CD56 and chromogranin. Results: EGFR protein overexpression was identified in 49 cases, by the application of Hirshs scoring system. The chromosome 7 and EGFR gene were analyzed by FISH and scored according to Cappuzzos method that showed high polysomy in 31 cases and amplification in 7 cases. Deletion in exon 19 of EGFR was detected in 3 cases of 48 samples; the exon 21 of EGFR was expressed in its wild type by RFLP in all cases. Conclusions: Detection of common EGFR deletion and mutation showed to be a rare event in Squamous cell carcinoma of the lung. While EGFR mutation is the most effective molecular predictor or sensitivity in patients with advanced NSCLC submitted to EGFR-TKIs treatment, amplification and polysomy is the most effective molecular predictor for EGFR-TKIs responsiveness in squamous cell carcinoma, when valida ted isolated from the group of NSCLC.